Patient experience in co-production of care: perceptions about patient safety protocols - Diovane Ghignatti da Costa; Gisela Maria Schebella Souto de Moura; Simone Silveira Pasin; Francis Ghignatti da Costa; Ana Maria Müller de Magalhães
Objective: to analyze the experience of the patient during hospitalization, focusing on the co-production of care related to patient safety protocols. Method: qualitative study, whose data were collected through the triangulation of multiple sources: document analysis, observation of 10 professionals in the provision of care and 24 interviews with patient-families from 12 clinical and surgical inpatient units of a hospital. Thematic analysis was carried out, based on the concept of co-production. Results: safety protocols according to the experience of the patient portrayed the role of patient-families as co-producers of safe care. It was found an alignment between perceptions of the patients, institutional definitions and basic national and international patient safety protocols. However, these protocols are not always followed by professionals. Conclusion: co-production was perceived in the protocols for safe surgery and prevention of injuries resulting from falls. In patient identification, hand hygiene and medication process, it was found that co-production depends on the proactive behavior of patient-families, as it is not encouraged by professionals. The research contributes with subsidies to leverage the participation of the patient as an agent of their safety, highlighting the co-production of health care as a valuable resource for advancing patient safety.